OCTOBER 16, WORLD FOOD DAY: MAKING INDIA FREE FROM HUNGER - Patel, Amrit (International Journal of Research -GRANTHAALAYAH, 2016)
Every year some parts of India witness droughts and floods directly impacting on food output. India experienced two drought years [July2014-June15 & 2015-16] impacting on low food output followed by 2016-17, a year of severe floods. As 36th World Food Day (WFD) will be observed on 16th October, 2016 India can size and capitalize this opportunity to redouble its efforts in creating awareness among all stakeholders by mounting a massive campaign to improve crop productivity per unit area and resources and eliminate hunger, poverty and rural unemployment. India could not achieve Millennium Development Goal-1 to half the percentage of hungry people by 2015. It has now committed to achieve the United Nations Sustainable Development Goal-2 target to “end hunger, achieve food security and improved nutrition, and promote sustainable agriculture” by 2030. In this context, this development perspective article highlights the current Indian scenario and suggests specific aspects to achieve the SDG-Goal 2 and make India free from hunger by 2030.